Alpha clustering in nuclear astrophysics and topology - Kahl, Daid; Yamaguchi, Hidetoshi; Hayakawa, Seiya (Frontiers in Physics, 2023)
When we think of clustering in nuclear physics, the astrophysical importance within light nuclei and the structural manifestations with classical analogs immediately come to mind. 4 He, also known as the alpha particle, is the most abundant nucleus in the Universe, being quite tightly bound for its mass, with a first excited state over 20 MeV. The nature of the alpha particle places it in a unique position within nuclear astrophysics and structure (including geometry). The plurality of energy release from stellar hydrogen fusion – whether quiescent or explosive – comes from the conversion of hydrogen to helium. Within more complex nuclei, alpha particles are continuously arranged, leading to fascinating phenomena such as excited rotational bands, Borromean ring ground states, linear structures, etc. Nuclei with an equal and even number of protons and neutrons are colloquially referred to as “alpha conjugate nuclei” where such special properties are the most pronounced and easiest to spot. However, when a single nucleon or a pair of nucleons are added to the system, the alpha clustering not only remains evident, but it may even be enhanced. Excited states with large alpha partial widths are a signature of clustering behavior, and these states can have a profound effect on the reaction rates in astrophysical systems when the excitation energy aligns with the so-called Gamow energy – the preferential thermal energy to statistically overcome the Coulomb barrier. In this article, we will consider in detail the specific ramifications of alpha clustering in selected scenarios for both nuclear astrophysics and topology. In particular, we discuss the astrophysical reactions of 7 Li(α, γ), 7 Be+α, 11 C(α, p), and 30 S(α, p), where α-clusters may increase the reaction rates from 10% to an order of magnitude; large α resonances makes the astrophysical rate of 18 F(p, α) quite uncertain. We also focus on the α rotational bands, of both positive and negative parity, of 11 B and 11 C, and finally on the strongest evidence for the linear chain cluster state observed in 14 C.